Tbx20 Induction Promotes Zebrafish Heart Regeneration by Inducing Cardiomyocyte Dedifferentiation and Endocardial Expansion - Fang, Yabo; Lai, Kaa Seng; She, Peilu; Sun, Jianjian; Tao, Wufan; Zhong, Tao P. (Frontiers in Cell and Developmental Biology, 2020)
Heart regeneration requires replenishment of lost cardiomyocytes (CMs) and cells of the endocardial lining. However, the signaling regulation and transcriptional control of myocardial dedifferentiation and endocardial activation are incompletely understood during cardiac regeneration. Here, we report that T-Box Transcription Factor 20 (Tbx20) is induced rapidly in the myocardial wound edge in response to various sources of cardiac damages in zebrafish. Inducing Tbx20 specifically in the adult myocardium promotes injury-induced CM proliferation through CM dedifferentiation, leading to loss of CM cellular contacts and re-expression of cardiac embryonic or fetal gene programs. Unexpectedly, we identify that myocardial Tbx20 induction activates the endocardium at the injury site with enhanced endocardial cell extension and proliferation, where it induces the endocardial Bone morphogenetic protein 6 (Bmp6) signaling. Pharmacologically inactivating endocardial Bmp6 signaling reduces expression of its targets, Id1 and Id2b, attenuating the increased endocardial regeneration in tbx20-overexpressing hearts. Altogether, our study demonstrates that Tbx20 induction promotes adult heart regeneration by inducing cardiomyocyte dedifferentiation as well as non-cell-autonomously enhancing endocardial cell regeneration.